1985
DOI: 10.1103/physrevc.32.1897
|View full text |Cite
|
Sign up to set email alerts
|

In-beam gamma-ray spectroscopy ofSr82

Abstract: The reaction 7o~e~160, 2p2n) Sr with E~160) 80 MeV was used to study the nucleus Sr. Measurements were made of the excitation functions, angular distributions, and y-y-t coincidences.From these measurements six new levels were placed in the level scheme of ' Sr at 2683.7, 3609.2, 4367.1, 5308.4, 6364.4, and 7827.8 keV. A gamma ray with a very high anisotropy [ A2 ---1.05 (7), Aq --0.12(6)] feeds the (11 ) level at 5914.5 keV; A new band based on the level at 3525.7 keV was identified. The sequence of transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 20 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…Evidences of large prolate deformations have also been found for 78980Sr from lifetime measurements (Lister etal 1982, Davies et al 1987, Heese et al 1990 and from many other experimental results (Theisen et al 1982, Ramayya el al 1988, Gross et al 1989. 82Sr has been studied by Haskins et al (1985) and Baktash et al (1991). Using the technique of atom-photon laser spectroscopy, Eastham et al (1987) have extracted the quadrupole deformation of proton-rich strontium isotopes.…”
Section: Introductionmentioning
confidence: 73%
“…Evidences of large prolate deformations have also been found for 78980Sr from lifetime measurements (Lister etal 1982, Davies et al 1987, Heese et al 1990 and from many other experimental results (Theisen et al 1982, Ramayya el al 1988, Gross et al 1989. 82Sr has been studied by Haskins et al (1985) and Baktash et al (1991). Using the technique of atom-photon laser spectroscopy, Eastham et al (1987) have extracted the quadrupole deformation of proton-rich strontium isotopes.…”
Section: Introductionmentioning
confidence: 73%
“…This signifies a shape transition from a deformed rotor at N = 38 to a spherical vibrator at N = 46, 48. Earlier studies have suggested that the energy level spacing for the ground state bands of 82 Sr show a vibrational like behavior and higher spins showing rotational structures [43]. But, Sr 80,82…”
Section: Energy Levelsmentioning
confidence: 92%
“…Gamma-ray spectroscopy continues to give new insight into the nuclear structure and remains a topic of interest over the decades [1][2][3][4][5]. The High Purity Germanium (HPGe) detector, having very good energy resolution is a powerful instrument for discrete γ-ray spectroscopy and remains the best apparatus for nuclear structure and astrophysics studies by making of HPGe array [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%